Preliminary Study on the Prominent Entrepreneurial Skills Set in the Context of Civil Engineering Practice - Entika, Christie Lanjing; Mohammad, Shahrin; Jabor, Mohd Khata; Osman, & Sharifah (Journal of Technical Education and Training, 2017)
Despite the fact that the importance of acquiring entrepreneurial skills for future engineers has been widely discussed, yet the specific prominent entrepreneurial skills set with respect to a specific context of interest were often left unexplained. A similar phenomenon has occurred in the context of engineering practice and possibly implying that the prominent entrepreneurial skills set in the context of civil engineering practice still remain ill-defined. As the need for engineers to acquire entrepreneurial skills to meet the economic and workforce requirements has been widely recognised, thus identifying the prominent entrepreneurial skills set in the context of civil engineering practice is very important. The purpose of this paper is to discuss the prominent entrepreneurial skills set in the context of civil engineering practice in reference to the recommendations by the American Society of Civil Engineers (ASCE). This preliminary study was conducted by having interviews with civil engineering practitioners and thematic analysis was used to analyse the data. The findings have shown the prominent skills in the entrepreneurial skill set are mostly acquired in the managerial tracks in the civil engineering practice.